(untitled) (INTEGRATION PROCEEDING, 2023)
Maternal mortality is still a serious health problem in Magetan Regency. According to data from the Magetan District Health Office in 2018, the biggest cause of death was bleeding with a percentage of 31% or 13 cases of death. The purpose of this study was to determine the dominant factor in the incidence of postpartum hemorrhage at dr. Sayyidiman hospital Magetan period 2015 - 2018. This research uses the descriptive research method. With a large sample, the total population (sampling quota) is 40 cases of postpartum hemorrhage. The variables of this study include age, parity, birth spacing, and anemia. The results showed that the age at risk for bleeding was 15%, parity was at risk of 5%, the delivery interval was at risk of 75%, and anemia was 65%. Spacing of risky deliveries and anemia are the dominant factors in the incidence of preeclampsia in pregnancy. The conclusion that can be obtained from this study is that risk factors for birth spacing with a percentage of 75% and anemia at 65% are the dominant factors for the incidence of postpartum hemorrhage in dr. Sayidiman hospital Magetan Period 2015-2018. As health workers, especially midwives, it is advisable to carry out careful screening so that complications do not occur, especially in postpartum hemorrhage. Pregnant women also need routine and regular pregnancy check-ups so that later complications do not occur during childbirth.